1997
DOI: 10.1076/phbi.35.3.207.13302
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Furanoeremophilanes from Senecio bonariensis

Abstract: Four toxic 10 ␣H-9-oxofuranoeremophilanes were isolated and identified from the petroleum ether extract of Senecio bonariensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…The reaction mixture was stirred at room temperature for 5 h, a solution of 10% NaOH (10 ml) was added and the resulting mixture was extracted with CH 2 Cl 2 . The organic layer was washed with 10% NaOH (3 ð 10 ml) and water until neutral pH, dried over anhydrous Na 2 SO 4 , filtered and evaporated to dryness. The residue was chromatographed over neutral alumina.…”
Section: Reduction Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction mixture was stirred at room temperature for 5 h, a solution of 10% NaOH (10 ml) was added and the resulting mixture was extracted with CH 2 Cl 2 . The organic layer was washed with 10% NaOH (3 ð 10 ml) and water until neutral pH, dried over anhydrous Na 2 SO 4 , filtered and evaporated to dryness. The residue was chromatographed over neutral alumina.…”
Section: Reduction Ofmentioning
confidence: 99%
“…2 The toxicity exhibited by these plants has been attributed to their content of pyrrolizidine alkaloids 2,3 and some furoeremophilanes. 4 Recently it has been reported that some cacalolides exhibit antihyperglycemic activity in mice, 5 are active against some phytopathogenic fungi 6 and show antimicrobial and antifeedant activity. 7 Cacalolides are biogenetic Wagner-Meerwein rearrangement products derived from furoeremophilanes, 8 the name of which is derived from cacalol (1), originally isolated from the antihyperglycemic species Cacalia decompositae.…”
Section: Introductionmentioning
confidence: 99%
“…The toxic metabolites are thought to be pyrrole derivatives of the pyrrolizidine alkaloids. However, recently some furoeremophylanes have also been described as toxic compounds …”
mentioning
confidence: 99%
“…However, recently some furoeremophylanes have also been described as toxic compounds. 7 Senecio madagascariensis Poir. (Compositae, Senecioneae), known as fireweed, is a plant of South African origin, 8 and many efforts have been made to control its infestation level in pastures.…”
mentioning
confidence: 99%
See 1 more Smart Citation